Penerapan Program Pustakawan Muda dan Duta Pustaka dalam Menumbuhkan Budaya Literasi Kelas XI MIPA 1 MAN 3 Kebumen - Sofiyaturrohmah, Sofiyaturrohmah; Arifah, Umi (IAINU Kebumen, 2025)
This research was carried out with the aim of knowing the implementation of the program pustakawam muda dan duta pustaka in improving the literacy culture of student in class XI MIPA 1 MAN 3 Kebumen. This research uses descriptive qualitative research. The data collection techniques used are observation, interviews, and documentation, using data analysis techniques, namely data reduction, data presentation and drawing conclusions. The research results obtained were, 1) the implementation stages of the program pustakawan muda dan duta pustaka have been carried out well and in accordance with Permendikbud No. 3 Of 2015 concerning character, the first stage is habituation in the form of monday morning literacy activities. The second stage is development, there are several activities including workshops, trolli gas, mandatory visits and mandatory loans. The third stage is learning, in the form of assigments from teachers that will make student literate. Literacy culture, especially class XI MIPA 1, as well as MAN 3 Kebumen students in general has improved with this proggram